2020
DOI: 10.3390/jcm9061889
|View full text |Cite
|
Sign up to set email alerts
|

Validation of FRIEND and ACSM Equations for Cardiorespiratory Fitness: Comparison to Direct Measurement in CAD Patients

Abstract: The regression equation of the American College of Sports Medicine (ACSM) was a preferred method for estimating maximal oxygen consumption (VO2max). Recently, a more precise equation from the fitness registry and the importance of exercise national database (FRIEND) for healthy people was developed. This study compared VO2max estimated by the ACSM and FRIEND equations to VO2max directly measured in coronary artery disease (CAD) patients. Overall, 293 CAD patients who participated in cardiac rehabilitation betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
2
11
1
Order By: Relevance
“…Measurement of indirect calorimetry was not available. VȮ 2 peak was estimated using the American College of Sports Medicine patients with coronary artery disease suggested a 16% and 20% overestimation of VȮ 2 peak in females and males, respectively, using the ACSM equation when compared to direct measurement (Jang et al 2020). The generalizability of these results is limited since only patients from one centre who underwent percutaneous coronary interventions (PCI) and had a good fitness level were recruited, and females represented only 22% of the sample.…”
Section: Estimated Vȯ 2 Peakmentioning
confidence: 99%
See 2 more Smart Citations
“…Measurement of indirect calorimetry was not available. VȮ 2 peak was estimated using the American College of Sports Medicine patients with coronary artery disease suggested a 16% and 20% overestimation of VȮ 2 peak in females and males, respectively, using the ACSM equation when compared to direct measurement (Jang et al 2020). The generalizability of these results is limited since only patients from one centre who underwent percutaneous coronary interventions (PCI) and had a good fitness level were recruited, and females represented only 22% of the sample.…”
Section: Estimated Vȯ 2 Peakmentioning
confidence: 99%
“…We recruited more females (n=40, 29%) than most HIIT-based CR evaluations (Way et al 2021) and captured the comprehensiveness of CR with several physical-and mental-health outcomes. The main limitation of our study is the estimation of VȮ 2 peak from ACSM equations instead of measuring it directly with ergospirometry; this approach is associated with a higher measurement error (Jang et al 2020), but is an affordable (Grace et al 2016b) and valid method to capture VȮ 2 peak improvements in cardiovascular populations (American College of Sports Medicine 2020). When possible, future sex-specific studies should utilize directly measured gas analysis to benefit from the greater sensitivity, which may be key for sex comparisons (Rengo et al 2020).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…13,[22][23][24] Functional capacity was calculated using the equation derived from the FRIEND registry, which has been applied to different protocols (including the Bruce and ramp protocols) in healthy populations and in those with coronary artery disease (CAD). 14,25,26 Its results are closer to the VO2 max measured through ergospirometry than to those obtained by the American College of Sports Medicine (ACSM) equation, which is still widely used. 14,25,26 Stress-induced arrhythmias are associated with a higher incidence of cardiovascular events and higher long-term mortality.…”
Section: Discussionmentioning
confidence: 50%
“…14,25,26 Its results are closer to the VO2 max measured through ergospirometry than to those obtained by the American College of Sports Medicine (ACSM) equation, which is still widely used. 14,25,26 Stress-induced arrhythmias are associated with a higher incidence of cardiovascular events and higher long-term mortality. [27][28][29][30][31] Jouven et al, 27 demonstrated that asymptomatic individuals who presented complex ventricular arrhythmias during the exercise period had 30 however, observed that the presence of ventricular arrhythmias at the recovery phase was associated with a worse prognosis when compared to the exercise phase, which is similar to what was found in a recent metaanalysis.…”
Section: Discussionmentioning
confidence: 50%